Alternative binary green oxidant application for environmentally friendly treatment of leachate membrane bioreactor effluent - Gun, Sebnem; Kurkcu, Cagla; Yilmaz, Rabia Nefise; Can-Guven, Emine; Guvenc, Senem Yazici; Varank, Gamze (ELSEVIER, 2025)
In this study, the treatability of leachate membrane bioreactor (MBR) effluent was investigated by CaO2/PS/Fe(II) and CaO2/PMS/Fe(II) processes. While existing studies focus on synthetic wastewater, this work evaluates CaO2/PS/Fe(II) and CaO2/PMS/Fe(II) processes for real leachate MBR effluent. The study will highlight the potential of using green oxidants and catalysts in the treatment. Environmentally friendly oxidants (CaO2, PS, and PMS) and environmentally friendly catalysts (Fe(II), which is defined as environmentally friendly with its properties such as low cost, abundance, low toxicity, and sustainability) were used. The COD removal efficiencies of binary processes were higher than those of single processes, and the highest COD removal efficiencies were achieved with combined processes. Box-Behnken Design (BBD) was applied to determine the effects of process variables on the combined processes. The optimum conditions were initial pH 6.92, Fe(II) dose 2.72 g/L, CaO2 dose 3.65 g/L, and PS dose 3.89 g/L for CaO2/PS/Fe(II) while initial pH 7.22, Fe(II) dose 2.74 g/L, CaO2 dose 3.37 g/L, and PMS dose 4.65 g/L for CaO2/PMS/Fe(II). Under optimum conditions, COD and UV254 removal were estimated as 89.5 % and 98.9 %, respectively for CaO2/PS/Fe(II) and 92.7 % and 99.7 %, respectively for CaO2/PMS/Fe(II). To verify the data, validation experiments were conducted and COD and UV254 removal were 87.5 % and 96.2 % for CaO2/PS/Fe(II) and 90.1 % and 97.6 % for CaO2/PMS/Fe(II), respectively. Minor deviations (<3 %) between predicted and experimental results are attributed to wastewater heterogeneity and experimental margins. Combined green oxidation processes effectively treated the leachate MBR effluent meeting the discharge criteria desired for the receiving media.
Keywords: Advanced oxidation; Calcium peroxide; Leachate; Peroxymonosulfate; Persulfate; ACTIVATED PERSULFATE OXIDATION; ASSISTED PERSULFATE; LANDFILL LEACHATE; DEGRADATION; KINETICS; UV; OXYTETRACYCLINE; PERFORMANCE; CATALYSTS; Engineering; Water Resources